2019
DOI: 10.1101/719906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous optimization of donor and acceptor substrate specificity for transketolase by a small but smart library

Abstract: A narrow substrate range is a major limitation in exploiting enzymes more widely as catalysts in synthetic organic chemistry. For enzymes using two substrates, the simultaneous optimization of both substrate specificities, is also required for the rapid expansion of accepted substrates. Transketolase catalyses the reversible transfer of a C2ketol unit from a donor substrate to an aldehyde acceptor and suffers the limitation of narrow substrate scope for widely industrial applications. Herein, transketolase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Recent studies showed that aliphatic αketoacids can be recognized as donor substrates by specially designed TK variants. [8] Particularly, the thermostable TK from Geobacillus stearothermophilus [9] has been engineered to accept pyruvate, 2-oxobutyrate, 3-methyl-2-oxobutyrate as donors in place of HPA (Scheme 1). Preparative scale syntheses were performed in the presence of glycolaldehyde and d-glyceraldehyde as acceptors leading to the corresponding deoxysugars.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that aliphatic αketoacids can be recognized as donor substrates by specially designed TK variants. [8] Particularly, the thermostable TK from Geobacillus stearothermophilus [9] has been engineered to accept pyruvate, 2-oxobutyrate, 3-methyl-2-oxobutyrate as donors in place of HPA (Scheme 1). Preparative scale syntheses were performed in the presence of glycolaldehyde and d-glyceraldehyde as acceptors leading to the corresponding deoxysugars.…”
Section: Introductionmentioning
confidence: 99%